PP21 Mortality change over time in European cities: a population-based longitudinal study of 80 million people. (2nd September 2014) - Richardson, EA; Moon, G; Pearce, J; Shortt, NK; Mitchell, R
Abstract : Background: An increasing proportion of Europe's population reside in cities, hence understanding urban health, and its determinants, is increasingly important. Processes at local, city, regional, national and wider scales interact in complex ways to influence the health of city populations. Previous studies of urban health in Europe have examined only a small number of cities, and have not considered influences at multiple scales. We explore how mortality change over time varies between European cities, assess the importance of influences at different spatial scales, and investigate the role of socio-economic differences in explaining the trends. Methods: City-level data on all-age all-cause mortality, and population age and sex structure were obtained for three waves of the European Urban Audit: 1999–2002, 2003–2006 and 2007–2009. The Urban Audit provides comparable data on quality of life across European cities. Standardised mortality ratios (SMRs, referenced to 2001) for each sex were calculated for 274 cities from 26 European countries (11 Eastern and 15 Western). Multilevel regression models (in Stata/IC 11.0) were used to model SMRs as a function of wave, and subsequently of gross domestic product (GDP) per capita for the local region (NUTS3). The sample population averaged 80 million. Results: SMRs declined over time for each city, and the East-West gap narrowed due to faster improvements in Eastern European (average overall SMR decreases of 19 points for males and 14 points for females) than Western European cities (12 and 9 point decreases respectively). The most rapid improvements occurred in cities with the highest initial mortality. Countries better captured mortality variation between European cities for females and Eastern European males than the cities themselves; country- and city-level differences accounted for an average of 70% and 21%, respectively, of the variance in these models. For Western European males the reverse was observed, with countries and cities accounting for an average of 33% and 59% of variance respectively. Regional GDP per capita was only related to change in city-level mortality for Western European males. Conclusion: This study finds that national and wider scale influences on health in cities are important. The findings suggest that male mortality in Western Europe is strongly influenced by the city-specific social and economic environment – such as labour markets – while mortality of females and Eastern European males is more sensitive to drivers at the national level, such as the welfare state. We highlight the importance of considering multiple scales of influence on health.